Cultural Tourism and Trade in Indigenous People’s Art and Craft: A Gap Analysis of International Legal Treatise and National Legislation - Ida Madieha bt. Abdul Ghani Azmi (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The United Nations Declaration on the Rights of the Indigenous People, adopted on 13 September 2007, provides a clear support for the recognition of indigenous people’s right over their cultural heritage, traditional cultural expression and traditional knowledge (Article 31). The Declaration which was supported by both Malaysia and Indonesia provides the framework for the evolution of laws, regulations and rules to maintain, develop the past and future manifestation of their cultural practices (Article 11). States are also expected to provide effective redress for the misappropriation of their cultural practices including restitution and repatriation of their ceremonial objects and human remains (Article 12).Indigenous culture is fast growing to be a major drawing appeal to global tourists. This paper commences with a brief expose on how the cultural practices of the indigenous people became a key attractions for tourist in Malaysia. The paper seeks to ask how cultural tourisms can pose harm to the cultural integrity of the indigenous people. The widespread sale of their arts and crafts and the lack of control over reproduction of cheap copies for tourists question the measures taken by the state to control the misappropriation of their cultural practices.  TCE has also been the subject of coverage in many other international treaties and domestic legislation. This paper examines the gaps between the various legal treatises on TCE and national legislation with the aim of fortifying the relevant rules for countries like Malaysia and Indonesia to emulate. The paper concludes with some suggestions for legislative reform for the effective control of trade in indigenous people’s art and crafts.